A gebra named Al - Isdell, Wendy, 1975- ([s.n.], 2017)
Trouble with her algebra homework leads Julie through a mysterious portal into the Land of Mathematics, where a zebra-like Imaginary Number and creatures representing Periodic Elements help her learn about math and chemistry in order to get home.